Engagement or Sustainability: Managerial Performance - Edy Jumady (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
This study is motivated by the importance of enhancing management performance by using budget participation and total quality management as influencing factors. This research was conducted by three building companies in the city of Makassar. 68 respondents understand quite broadly the use of primary and perceptual data. The findings showed that, when the dominant variable was budgetary participation, the two independent variables had a positive relationship and a significant impact on management performance. Although several earlier studies have supported the results of the study, one of the next questions to be answered is the principle of significance of each element in the company, as management performance does not mean that firm value is directly responded to in a positive way.